sodA and gap Genes as Markers for The Identification of Staphylococcus capitis - Rininta Firdaus; Hege Hartz Jartun; Miriam Khider (The Indonesian Biomedical Journal, 2019)
BACKGROUND: Rapid and accurate identification of Staphylococcus capitis is required to provide a better prognosis for endocarditis patients and tackle the emergence of multidrug resistant strains of the bacteria in hospitals. The current study was aimed to develop polymerase chain reaction (PCR) assay for specific identification of S. capitis using sodA and gap genes as markers.METHODS: Five sequences of sodA and sixteen sequences of gap registered in GeneBank were analysed using bioinformatic tools. PCR primers were designed based on the conserved and specific regions of sodA and gap. Four clinical isolates of S. capitis (named no. 56-59) and six reference strains of coagulase-negative staphylococci (CoNS) species including S. epidermidis ATCC 35984, S. epidermidis 48951I/09, S. lugdunensis 44987/09, S. sciuri 109645I/08, S. warneri 135612/09, S. hominis 114202/08 were used to validate the conventional PCR system.RESULTS: The current PCR system only amplified the DNA template of S. capitis. Current primers specifically targeted S. capitis as the agarose images only showed bands from S. capitis samples.CONCLUSION: The sodA and gap genes might serve as effective markers for identification of S. capitis using conventional PCR. The PCR assay in the current study was able to identify five clinical isolates of S. capitis accurately without mispriming, misamplification and misidentification. The PCR system was also able to discriminate other CoNS including S. epidermidis, S. lugdunensis, S. sciuri, S. warneri and S. hominis.KEYWORDS: Staphylococcus, S. capitis, sodA, gap, PCR